Effect of green tea catechins on the pharmacokinetics of digoxin in humans - Kim, Tae-Eun; Shin, Kwang-Hee; Park, Jeong-Eun; Kim, Min-Gul; Yun, Yeo-Min; Choi, Dong-Hee; Kwon, Kyoung Ja; Lee, Jongmin (Drug design, development and therapy, 2018)
Previous in vitro studies have reported the inhibitory effect of green tea on p-glycoprotein (p-gp) encoded by . This study aimed to investigate the effect of green tea on the pharmacokinetics of digoxin, a typical probe drug of p-gp. Sixteen healthy volunteers participated in this study. At Day 1, 0.5 mg of digoxin was administered via oral route. After a 14-day washout period, 630 mg of green tea catechins (GTC) was administered via oral route, followed by 0.5 mg of digoxin 1 hour later. From Day 16 through Day 28, 630 mg of GTC was administered alone. At Day 29, 630 mg of GTC and 0.5 mg of digoxin were administered in the same way as Day 15. Blood samples for the pharmacokinetic assessments of digoxin were collected up to 8 hours after each dose. Pharmacokinetic parameters were estimated by noncompartmental analysis. Area under the curve (AUC) and peak plasma concentration ( ) were compared using mixed effect model between digoxin alone and digoxin with GTC. was genotyped to determine whether its polymorphism affects digoxin-GTC interaction. Fifteen subjects completed the study. Compared to digoxin alone, the concomitant administration of digoxin and GTC significantly reduced the systemic exposure of digoxin: geometric mean ratios (GMR) and 90% confidence intervals (CI) of area under the concentration-time curve from time 0 to the last measurable time (AUC ) and were 0.69 (0.62-0.75) and 0.72 (0.61-0.85), respectively. The concomitant administration of digoxin and GTC following pretreatment of GTC (Day 29) similarly reduced the AUC (GMR [90% CI]: 0.67 [0.61-0.74]) and (GMR [90% CI]: 0.74 [0.63-0.87]). In the comparison of the percentage changes from Day 1 (digoxin single administration) of AUC between genotypes, C1236T variant type showed a significant difference to wild-type on Day 15 (concomitant administration of digoxin and GTC) ( =0.005). This study demonstrates that the coadministration of GTC reduces the systemic exposure of digoxin regardless of pretreatment of GTC.